Nutritional and Microbial Quality of Mango-based Cereal Flakes Stored at Different Temperatures: Nutritional and microbial quality of mango cereal flakes - Saddozai, Ambreen Akhtar; Mumtaz, Amer; Raza, Saeeda (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
Malnutrition in young children is a serious problem in Pakistan. In a recently carried out nutritional survey in the country, more than 44% of children, under five years, have been observed to be stunted and underweight. Because of their palatable taste and convenience of intake, snacks are a popular food item amongst children, but such food products may lack essential nutritional and hygiene quality. In order to address child malnutrition by catering nutritious and hygienic food, an instant food product was developed using cereals (i.e. wheat, suji, corn and rice) and mango pulp, blended in various proportions, to form cereal flakes for preparing a likable snack for children consumption. The ingredients (i.e., cereal paste, mango pulp, salt and ghee) were mixed, cooked and passed through a homogenizer to obtain a uniform mix. The mixture was cooked on a drum dryer (at steam pressure of 60 lb./sq. inch) to obtain long thin sheets, which were later broken manually into small pieces. The pieces were dried at 50 o C for an hour in a dehydrator to reduce their moisture content to about 2 percent and then were packed in high density polyethylene zipper bags. The rice-mango flakes were found to be highly acceptable for sensory attributes. They were stored for 180 days at two different temperatures, i.e., 25 ° C and 37 ° C, in a controlled temperature cabinet and the changes in nutritional and microbiological attributes were monitored at 30-day intervals. It was observed that moisture, protein, crude fat and carotene content in the flakes decreased significantly with increase in storage period (P<0.05) while total plate count remained within the permissible range at both temperatures till 150 days of storage. However, significant changes in total plate count were observed beyond 150 days. Total coliform, yeast and mold content could not be detected till 180 days of storage time at both temperatures. Thus, the mango-based cereal flakes remained nutritionally and microbiologically acceptable up to 150 days of storage both at 25 °C and 37 °C.